2017
DOI: 10.1038/s41598-017-04552-5
|View full text |Cite
|
Sign up to set email alerts
|

The life-course impact of smoking on hypertension, myocardial infarction and respiratory diseases

Abstract: The objective of this study was to examine the impact of smoking on respiratory diseases, hypertension and myocardial infarction, with a particular focus from a life-course perspective. In this study, 28,577 males from a Chinese longitudinal survey were analysed. The effects of smoking on the risk of respiratory diseases, hypertension and myocardial infarction were assessed from a life-course perspective and a current view separately. No significant associations were found between smoking and the risk of incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 50 publications
10
70
4
Order By: Relevance
“…Meanwhile the non-smokers have a higher proportion of having hypertension stage 2. This study have a contradicting result with other study which stated that smoking habit can increase blood pressure (Leone, 2015;Gao et al, 2017).…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…Meanwhile the non-smokers have a higher proportion of having hypertension stage 2. This study have a contradicting result with other study which stated that smoking habit can increase blood pressure (Leone, 2015;Gao et al, 2017).…”
Section: Resultscontrasting
confidence: 90%
“…On the other hand 27.9% of the subjects did not have any intention to stop smoking with the reason that they felt weak, sick, not good, dizzy, and sleepy if they did not smoke, feeling difficult to stop smoking because they were addicted, inhibiting social communication, often being offered cigarettes by other parties, and to get rid of bad smell in the mouth. Many studies revealed that smoking habit can arouse various kinds of diseases, such as respiratory diseases (Jayes et al, 2016), cardiovascular diseases (Mons et al, 2015), high blood pressure (Gao et al, 2017), and cancer (Proctor, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from the Shandong province [ 24 ] suggested that dietary salt intake is high, especially in rural areas, and has not changed much in the province over the past 10 years. Other risk factors for hypertension included age, overweight, obesity [ 38 40 ] and modifiable lifestyle factors, such as alcohol consumption [ 41 , 42 ] and smoking [ 43 , 44 ], which are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…A study conducted by Gao et al, also reported that life course adjusted smoking consumption is significantly positively associated with risks of hypertension. 37 Findings of a study conducted by Pietiläinen et al, showed that the risk of general obesity (OR 3.9) and especially central obesity (OR 4.8) significantly increases in physically inactive adolescents. 38 Experimental evidence from interventional studies have also confirmed a relationship between physical activity and hypertension as the exercise reduces blood pressure have been well characterized in recent years.…”
Section: Discussionmentioning
confidence: 98%